A Delayed Anatomic Diagnosis and Management Challenge in an Initially Asymptomatic Infant With Type II Pulmonary Artery Sling: A Case Report - Shi, Xiaoqing; Wang, Chuan; Hua, Yimin; Liu, Xiaoliang; Duan, Hongyu (Frontiers in Cardiovascular Medicine, 2021)
Pulmonary artery sling (PAS) is a rare but fatal malformation. Patients with PAS tend to develop obstructive symptoms in few weeks of life. Conversely, some patients may be otherwise mild or asymptomatic in their early life. Currently, no consensus on the intervention timing and treatment strategy for asymptomatic and mild cases has been reached. Moreover, the extent of tracheal stenosis is another determining factor for the choice of intervention timing since clinical symptoms might not correspond well with degree of stenosis. Lack of comprehensive assessment of entire airways confer underestimation of disease severity and in turn improper choice of treatment regimens as well as poor outcomes. Herein, we described an infantile case of PAS, who was scheduled initially for periodic outpatient follow-up on account of the absence of symptoms and inadequate imaging assessment at diagnosis. She developed recurrent wheezing and progressive respiratory distress at 7 months of age. After left pulmonary artery reimplantation without tracheal intervention, bronchoscopy was performed due to failure to wean from mechanical ventilation, which demonstrated complete tracheal cartilage rings, a long segment tracheal stenosis, a low tracheal bifurcation at T6, and absence of a separate right middle lobe bronchus. The patient was finally diagnosed with typeⅡb PAS, and extubated successfully following conservative treatment. Miserably, neurological sequelae were devastating, leading to the poor outcome. Comprehensive airway evaluation using bronchoscopy is substantial to early identification of all components responsible for airway compromise in PAS anatomic subtypes. Considering severe concomitant maldevelopment of the bronchial tree in children with typeⅡb PAS, early and complete correction by surgery might decrease perioperative morbidities and mortalities of these patients.